Merencanakan Sumber Belajar Berbasis Keterampilan Berperspektif Islami untuk Pendidikan Keanekaragaman Hayati - Setyowati, Eni (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2014)
Educators are beginning to recognize the importance and benefits of introducing pupils to biodiversity and associated issues. Generic criteria for successfully planning and developing a skills-based resource for Islamic perspective biodiversity education are described. The criteria presented here are general to be applied to any biodiversity education and they form a useful framework to construct a resource. Without such a framework there is danger that the biodiversity concept could be misrepresented.